The effect of tree species on soil organic carbon stock in Mongolian forest (Mongolian Journal of Geography and Geoecology, 2025)
Forest ecosystems in Mongolia play a critical role in storing soil organic carbon (SOC), a key component in mitigating climate change. However, little is known about how SOC stocks vary with dominant tree species in these forests. This study investigates the impact of tree species on SOC stocks in Mongolia’s boreal forests, focusing on four commonly found species: Larix sibirica, Pinus sylvestris, Pinus sibirica, and Betula platyphylla. Data were compiled from 885 soil samples across 177 soil profiles, representing diverse forest ecosystems. SOC stocks were standardized to two depth intervals (0–30 cm and 30–60 cm) using a weighted averaging method. Statistical analyses, including as ANOVA and Principal Component Analysis (PCA),  were conducted to determine species-level differences and the influence of environmental factors. Results show significant variation in SOC stocks among species (F = 8.79, p < 0.001), with Betula platyphylla exhibiting the highest mean SOC stock (110.1 Mg C ha⁻¹) and Pinus sylvestris the lowest (64.2 Mg C ha⁻¹). SOC stocks generally decreased with depth across all species, though Pinus sylvestris showed higher subsurface SOC than in surface layers, likely due to deeper root systems in sandy Arenic Podzols. PCA revealed that SOC in surface layers is positively influenced by slope, temperature, and precipitation, while subsurface SOC is more closely associated with latitude and elevation. The study highlights the role of tree species and site-specific conditions in shaping SOC dynamics, emphasizing the need to consider forest composition in carbon management and climate adaptation strategies in Mongolia.